USING COOPERATIVE INTEGRATED READING ANDCOMPOSITION (CIRC) MODEL IN READING COMPREHENSION - Benedicta Cindy Tamara, - (2023)
This study focuses on determining the effectiveness of applying the Cooperative Integrated Reading and Composition (CIRC) model in reading comprehension, especially in composing recount text. It focuses on finding solutions to the students' reading issues in relation to the four aspects including topic, grammar, meaning, and vocabulary. The pre-experimental research design was used to carry out this research. Pre-test observations in class were also carried out by researchers before implementing the CIRC model. After carrying out the pre-test, the researcher continued to apply the CIRC model in class. Random sampling was used with 30 students of VIII D Secondary School in Bandung. During the course of the investigation, the researcher observed classes and administered reading assessments to students, including pre-test and post-test. The results of this research indicated that CIRC use both individually and in groups significantly helps students' reading comprehension abilities. It was shown that the students' active participation in the implementation of CIRC model enhanced their reading comprehension abilities. Students also demonstrated positive outcomes towards numerous activities and features of the CIRC model. Keywords: CIRC model; reading comprehension; recount text